Association Cystatin C and Risk of Stroke in Elderly Patients With Obstructive Sleep Apnea: A Prospective Cohort Study - Su, Xiaofeng; Gao, Yinghui; Xu, Weihao; Li, JianHua; Chen, Kaibing; Gao, Yan; Guo, JingJing; Zhao, LiBo; Wang, Huanhuan; Qian, Xiaoshun; Lin, Junling; Han, Jiming; et al. (Frontiers in Neuroscience, 2021)
Abstract Background Few prospective cohort studies have assessed the relationship between Cystatin C(Cys-C) and risk of stroke in elderly patients with obstructive sleep apnea (OSA). The study sought to examine the association between baseline serum Cys-C and long-term risk of stroke among elderly OSA patients. Methods A total of 932 patients with OSA, no history of stroke, ≥60 years of age, and complete serum Cys-C records were included in this study. All patients had completed polysomnography (PSG). OSA was defined as an apnea-hypopnea index(AHI) of ≥5 events per hour. Participants were categorized into four groups according to baseline serum Cys-C concentration, split into quartiles. Multivariate Cox regression were used to evaluate the association between Cys-C and the incidence of new-onset stroke. Results Stroke occurred in 61 patients during the median 42-month follow-up period. The cumulative incidence rate of stroke was 6.5%, which included 54 patients with ischemic stroke and 7 patients with hemorrhagic stroke. The cumulative incidence of stroke was higher among patients with baseline serum Cys-C concentration of ≥1.15mg/L when compared with other groups (PLog-rank < 0.001). After adjusting for potential confounding factors in the Cox regression model, patients with a serum Cys-C concentration of ≥1.15mg/L had a 2.16-fold higher risk of developing stroke compared with patients with serum Cys-C ≤ 0.81mg/L (HR, 2.16, 95%CI, 1.09–6.60; P =0.017). Additionally, there was a higher risk in those of age ≥70 years (HR, 3.23, 95%CI, 1.05–9.24; P =0.010). The receiver-operating characteristic curves showed that the capability of Cys-C to identify elderly patients with OSA who had a long-time risk of stroke was moderate (AUC = 0.731, 95% CI: 0.683−0.779, P = 0.001). Conclusion Increased Cys-C concentration was identified as a risk factor in the incidence of stroke in elderly patients with OSA, independent of gender, BMI, hypertension and other risk factors. Additionally, it conferred a higher risk in patients of age ≥70 years.